“Looking at the World, I Spot Small Details”: the Researcher‘s View on Folklore, Mythology, and Local Culture. A conversation with the National Jonas Basanavičius Prize Winner for 2023 Daiva Vaitkevičienė - Leparskienė, Lina (Tautosakos darbai, 2024)
-